Low extinction risk for an important plant resource: Conservation assessments of continental African palms (Arecaceae/Palmae) - (:unkn) unknown (My University, 2018)
Although the palm flora of continental Africa totals just 66 species, they are amongst the most useful plants across the continent, providing many important resources for human populations. Studies have shown that African palms will likely be negatively affected by global change, leading to increased threats to their survival. Here we conduct the first full global conservation assessment for 61 continental African palm species following IUCN Red List Categories and Criteria. Our study revealed that fewer than 10% of the evaluated species were assessed as Threatened. Within the Threatened category, one species was assessed as Critically Endangered, three as Endangered and two as Vulnerable. These results underline an overall low extinction risk for African palms in the immediate future, which is substantially lower than the global estimate of 21% for all plants. These results could be linked to the generally large distribution patterns of African palm species, the broad ecological amplitudes of most species and their good representation inside the African protected areas network. However, a non-negligible number of species (~15%) lack sufficient data to be properly assessed. This highlights the importance of further studies to improve our basic understanding of their distribution and threats. Our study provides a rather optimistic view of this highly important African plant resource yet, some widespread species are becoming locally rare due to over-harvesting for human use. At a local level, palm resources are generally non-sustainably exploited, which, coupled with climate change, could lead to a rapid increase in threat status over time.
Keywords: African Research